An analogue of the logarithmic (u,v)-derivative and its application - Osaulenko, R. Y. (Methods of Functional Analysis and Topology, 2020)
We study an analogue of the logarithmic (u,v)-derivative. The last one has many interesting properties and good ways to calculate it. To show how it can be used we apply it to a model class of nowhere monotone functions that are composition of Salem function and nowhere differentiable functions.